Ker family interviewed by Jenny Salmon for the New South Wales Western Division oral history project. - Ker family; Salmon, Jenny (1983)
Talking about the stone homestead build by the Quinn family.
Recorded on 31 July 1983 at Turella station outside White Cliffs, N.S.W.
Digital master available
Keywords: Ker family -- Interviews; Country life -- New South Wales -- Western Division; Western Division (N.S.W.) -- History; Western Division (N.S.W.) -- Social conditions